Dumbbell-shaped block copolymers for the fabrication of anisotropic soft actuators - Pan, Houwen Matthew (2022)
The self-assembly of bottlebrush or comb copolymers into well-ordered structures can be accurately controlled to create functional materials for smart elastomeric actuators. However, to date, bottlebrush or comb copolymer self-assemblies have only been utilized in fabricating isotropic actuators. In this work, we report on the first synthesis of anisotropic soft actuators from comb triblock copolymers. Dumbbell-shaped comb block copolymers (BCPs) with poly(dimethylsiloxane) (PDMS) side chains were crosslinked via poly(butyl acrylate) (PBA) to form actuators that exhibited reversible actuation, fast response (5 min), a high anisotropic swelling strain (51% in the x-axis and 98% in the y-axis), and bending on the z-axis in an organic solvent. Characterization of anisotropic actuator strips pointed to a lamellar-like arrangement of PBA segments sandwiched between PDMS layers. Anisotropic swelling was programmed in single-layer actuators through shear-induced alignment (x-y axis) and phase separation (z-axis) of dumbbell-shaped BCPs without any additional patterning steps. Actuator bending was also significantly increased (330°) via the orthogonal arrangement of anisotropic bilayers.